PENGARUH STANDARD PELATIHAN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA PEGAWAI PADA PANTI SOSIAL BINA NETRA “TAN MIYAT” BEKASI - Mochamad Soelton; Siti Mutia Hardiati (Jurnal Ilmiah Manajemen dan Bisnis, 2017)
This study aims to determine how the Effect Standard Training Work And OrganizationalCitizenship Behavior Toward Employee Performance On Social Institution Bina NetraTan Miyat Bekasi Ministry of Social Affairs the results of this research uses descriptivequantitative approach with Non probality Sampling method that uses ConvienenceSampling. Data collection using the questionnaire and subsequent analysis of data usingmultiple linear regression.whereas data processing for the Test Do With SPSS Statistics21. The results of this study indicate that both independent variables (variables andvariable training organization citizenship behavior) positive and significant effect onemployee performance